HTTP behavior characteristics generation and extraction approach for Android malware - Yaling LUO; Wenwei LI; Xin SU (Dianxin kexue)
Growing of Android malware，not only seriously endangered the security of the Android market，but also brings challenges for detection.A generation and extraction approach of automatic Android malware behavioral signatures was proposed based on HTTP traffic.Firstly，the behavioral signatures were extracted from the traffic traces generated by Android malware.Then，network behavioral characteristics were extracted from the generated network traffic.Finally，these behavioral signatures were used to detect Android malware.The experimental results show that the approach is able to extract Android malware network traffic behavioral signature with accuracy and efficiency.